SOME ISSUES OF OVERCOMING OF GEGHARKUNIK PROVINCE DISPROPORTIONATE DEVELOPMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2020)
One of the priority goals of socio-economic development of the republic of Armenia is the overcoming current disproportional development and ensuring more or less balanced development of the territories. Disbalanced territorial development problems of Gegharkunik Province are discussed in the article.
Keywords: Gegharkunik province; balanced development; settledness; organic agriculture; territorial recreational system; alternative energy